Analisis Faktor-Faktor Yang Mempengaruhi Nilai Informasi Pelaporan Keuangan Pada Badan Pengelolaan Keuangan dan Aset Daerah Kabupaten Tolikara - Kodon, Klemens; Safkaur, Otniel; Ngutra, Risky Novan; Salle, Hesty Theresia (Universitas Cenderawasih, 2023)
This study aims to analyze the factors that affect the value of financial reporting information. Factors that affect the value of financial reporting information are measured by variables of human resource quality, information technology utilization, internal control systems, regional financial supervision. The research approach used is associative. The sampling technique used in this study was a saturated sample with the number of respondents as many as 60 people at the Regional Financial and Asset Management Agency of Tolikara Regency. Data collection is carried out by distributing questionnaires. Data analysis using multiple linear regression with the help of SPSS. This study provides results that partially human resources, the use of information technology and regional financial supervision do not have a significant effect on the value of financial reporting information, while the internal control system has a positional effect on the value of financial reporting information. Human resources, internal control systems, the use of technology and information, and regional financial supervision simultaneously affect the value of financial reporting information.